(untitled) (Journal of Management and Social Sciences, 2020)
This article provided insights into the factors affecting grassroot political participation in Nigeria, with a focus on Osun State. The study adopted survey research design and utilized primary data obtained through the administration of questionnaires and conduct of in-depth interview. A proportional fraction of 382 respondents comprising executive members of political parties, traditional chiefs, community development associations, civil society organizations and semi-formal organizations were selected for the study. The data were analysed using descriptive analysis with the aid of SPSS. The study revealed that limited government accommodation and responsiveness, lack of access to information about government programmes, lack of trust in political office holders, and low awareness level of the people concerning their roles in governance are major factors responsible for low grassroot participation in the governance of the State. These factors, as revealed, have led to the reduction of the legitimacy and peoples’ trust in the government of the State. Thus, more fora such as town hall meetings must be provided by the government and there should be a law for mandatory public hearing and consultation in the State.